Pelaksanaan Hak dan Kewajiban antara Pengusaha dan Pekerja dalam Perjanjian Kerja Bersama Ditinjau dari UU No. 13 Tahun 2003 tentang Ketenagakerjaan (Studi pada PT. Handsumtex, Tangerang) - Thorik, Sylvia Hasanah (Multiverse: Open Multidisciplinary Journal, 2023)
This research aims to assess the employer-employee rights and obligations in collective labor agreements according to Law no. 13 of 2003. Qualitative methods, including literature review and field research at PT. Handsumtex Tangerang, were employed. Findings reveal that: (a) The negotiation process for the 2015-2016 Collective Labor Agreement involved PT. Handsumtex and the trade union FSPTSK – SB HST, representing over 50% of the workers. The agreement, validated upon signing, is legally binding and registered with the Tangerang City Government Employment Service under registration number 568.2/5416-HI/2015. (b) Implementation of the agreement at PT. Handsumtex has seen minimal violations, primarily concerning overtime, resolved through negotiation as stipulated in Article 14. Administrative recording errors were identified, but no rights violations occurred.